Pernerapan Algoritma Multilevel Feedback Queue (MFQ) & First In First Out (FIFO) pada Studi Kasus di Toko Bunga ARTHA PUSPA - Candra Pamungkas; Angga Riyandi Saputra; Aditya Ramadhan; Alif Kurniawan; Naufal Abi Pratama; Wishnu Rindra (Yayasan Literasi Sains Indonesia, 2023)
Artha Puspa is a flower shop in Madiun which sells plant needs. This very rapid business development encourages every entrepreneur to create a form that is different from other businesses, one of which is the Arta Puspa Flower Shop, a common problem that is often experienced by Artha Puspa, namely direct purchase queues and orders. With that we use a combination of MFQ and FIFO. The application of a combination of Multilevel Feedback Queue (MFQ) and First In First Out (FIFO) algorithms is a strategy that can be used to manage processes that occur in computer systems. MFQ is a scheduling algorithm that uses several levels of queues, each of which has a different priority. Each process will be placed in a queue level according to its priority. Meanwhile, FIFO is a scheduling algorithm that manages processes by issuing processes that apply a combination of multilevel feedback queue (MFQ) & first in first out (FIFO) algorithms in the case study of the Bunga Artha Puspa store to enter the system for the first time. The combination of the two algorithms can provide a more effective solution in managing processes in computer systems. MFQ is a scheduling algorithm that uses several levels of queues, each of which has a different priority. Each process will be placed in a queue level according to its priority. Meanwhile, FIFO is a scheduling algorithm that manages processes by issuing processes that apply a combination of multilevel feedback queue (MFQ) & first in first out (FIFO) algorithms in the case study of the Bunga Artha Puspa store to enter the system for the first time. The combination of the two algorithms can provide a more effective solution in managing processes in computer systems. MFQ can be used to manage high priority processes, while FIFO can be used to manage low priority processes. Thus, processes that have high priority will always be processed first, thereby increasing system efficiency. In addition, the combination of MFQ and FIFO can also help reduce the waiting time for processes that have low priority, thereby increasing user satisfaction.